2012
DOI: 10.1371/journal.pone.0052191
|View full text |Cite
|
Sign up to set email alerts
|

Increasing Exercise Intensity Reduces Heterogeneity of Glucose Uptake in Human Skeletal Muscles

Abstract: Proper muscle activation is a key feature of survival in different tasks in daily life as well as sports performance, but can be impaired in elderly and in diseases. Therefore it is also clinically important to better understand the phenomenon that can be elucidated in humans non-invasively by positron emission tomography (PET) with measurements of spatial heterogeneity of glucose uptake within and among muscles during exercise. We studied six healthy young men during 35 minutes of cycling at relative intensit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
39
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(43 citation statements)
references
References 50 publications
4
39
0
Order By: Relevance
“…Previous studies have shown altered GUh as a result of increased exercise intensity [11], disease status [32], and motor unit remodeling due to aging [10]. Our results showed no difference between the groups in GUh for any muscle, which demonstrates similar fiber recruitment between groups.…”
Section: Discussionsupporting
confidence: 64%
See 3 more Smart Citations
“…Previous studies have shown altered GUh as a result of increased exercise intensity [11], disease status [32], and motor unit remodeling due to aging [10]. Our results showed no difference between the groups in GUh for any muscle, which demonstrates similar fiber recruitment between groups.…”
Section: Discussionsupporting
confidence: 64%
“…GUh of each ROI was calculated using the following equation: GUh = (standard deviation [SD] / SUV mean ) × 100 [10][11]. The volume of each ROI was calculated from the CT images using Analyze 11.0 and converted from millimeters cubed to centimeters cubed for analysis.…”
Section: Positron Emission Tomography/computed Tomography Imaging Anmentioning
confidence: 99%
See 2 more Smart Citations
“…Usually, surface electromyography (SEMG) is used to measure muscle activation, and is an essential tool in biomechanical and biomedical investigations [28]. In addition, it is widely revealed that electromyographic signals are generated in the human skeletal muscle during muscle fiber contraction, which is always random [36,42].…”
Section: Introductionmentioning
confidence: 99%